Mourning in America : race and the politics of loss - McIvor, David Wallace (Cornell University Press, 2016)
"Recent years have brought public mourning to the heart of American politics, as exemplified by the spread and power of the Black Lives Matter movement, which has gained force through its identification of pervasive social injustices with individual losses. The deaths of Sandra Bland, Michael Brown, Freddie Gray, Trayvon Martin, Tamir Rice, Walter Scott, and so many others have brought private grief into the public sphere. The rhetoric and iconography of mourning has been noteworthy in Black Lives Matter protests, but David W. McIvor believes that we have paid too little attention to the nature of social mourning--its relationship to private grief, its practices, and its pathologies and democratic possibilities. In Mourning in America, McIvor addresses significant and urgent questions about how citizens can mourn traumatic events and enduring injustices in their communities. McIvor offers a framework for analyzing the politics of mourning, drawing from psychoanalysis, Greek tragedy, and scholarly discourses on truth and reconciliation. Mourning in America connects these literatures to ongoing activism surrounding racial injustice, and it contextualizes Black Lives Matter in the broader politics of grief and recognition. McIvor also examines recent, grassroots-organized truth and reconciliation processes such as the Greensboro Truth and Reconciliation Commission (2004-2006), which provided a public examination of the Greensboro Massacre of 1979--a deadly incident involving local members of the Communist Workers Party and the Ku Klux Klan"--Publisher's Web site